Tuberculosis and histoplasmosis co-infection in AIDS patients (2012)
ABSTRACT : Coinfection with tuberculosis in some countries occurs in 8–15% of human immunodeficiency virus (HIV)-infected patients who have histoplasmosis. This coinfection interferes with prompt diagnosis, and treatment is difficultbecause of drug interactions. We retrospectively reviewed the cases of 14 HIV-infected patients who had concomitanttuberculosis and histoplasmosis. The most frequent clinical manifestations were weight loss (85.7%), asthenia (78.5%),and fever (64.2%). The diagnosis of histoplasmosis was made primarily by histopathology (71.4%), and the diagnosis oftuberculosis was made by means of direct microscopic examination (71.4%). Death occurred in two patients, and relapseof both infections occurred in one patient. Moxifloxacin was substituted for rifampicin in six patients, with goodoutcomes noted for both infections. The clinical presentation does not readily identify acquired immunodeficiencysyndrome (AIDS) patients who have tuberculosis and histoplasmosis. The use of a fluoroquinolone as an alternativeagent in place of rifampicin for tuberculosis allows effective therapy with itraconazole for histoplasmosis.